Liability for infringement of intellectual property rights - PUSTOVIT Юлія; KORENYUK Ольга (Ius Modernum, 2023)
Introduction. The institution of administrative responsibility for the violation of rights to intellectual property objects is particularly relevant in modern society: it is imperative to comply with the legislation to ensure fair competition in business activities, stimulate intellectual creativity and create conditions for the development of the economy of Ukraine. Problem. On the example of a specific court case, legislative gaps were identified, which lead to situations when the subject of entrepreneurial activity has to defend his intellectual property rights himself, and the violator is not even brought to administrative responsibility. The aim. The research is aimed at determining the problems of administrative responsibility for the violation of rights to intellectual property objects in modern conditions and identifying their features. Methods. General scientific and special methods of cognition are applied: historical, abstract-logical and comparison; analysis and synthesis, analogy, system approach; theoretical generalization and formulation of conclusions. Results. Judges often make mistakes in determining the object of illegal actions, which leads to incorrect decisions, in particular with regard to the confiscation of things that are not illegally manufactured and are not equipment or materials for the illegal manufacture of products. The Resolution of the Supreme Court is analysed, which is an example of the fact that a business entity must, through the court, terminate the violation of its rights to intellectual property, which arose as a result of the adoption of an individual act by the subject of authority. Conclusions. One of the problems of administrative proceedings in cases related to the violation of rights to intellectual property objects is the failure to bring the subjects of authority to justice: in the case under consideration, such a subject adopted an illegal individual act on the registration of a trademark, with which he violated the intellectual property rights of another business entity. The question of bringing to justice those responsible for what has become the subject of a legal dispute remains open.